2015
DOI: 10.3346/jkms.2015.30.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Prenatal Care, and Delivery of Mothers with Disabilities in Korea

Abstract: The aim of this study was to investigate the whole picture regarding pregnancy, prenatal care, obstetrical complications, and delivery among disabled pregnant women in Korea. Using the data of National Health Insurance Corporation, we extracted the data of women who terminated pregnancy including delivery and abortion from January 1, 2010 to December 31, 2010. Pearson's chi-square test and Student-t test were conducted to examine the difference between disabled women and non-disabled women. Also, to define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
2
5
0
3
Order By: Relevance
“…People with a mental or physical impairment had a higher smoking rate than an age- and sex-matched random sample from the general population [19], although health-related behaviors varied across types of disabilities [20]. Pregnant women with disabilities were found to be more likely to receive inadequate prenatal care than non-disabled pregnant women [21]. Several Korean studies have suggested that people with disabilities are prone to experience poverty, deprivation of human rights, social isolation, and discrimination [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…People with a mental or physical impairment had a higher smoking rate than an age- and sex-matched random sample from the general population [19], although health-related behaviors varied across types of disabilities [20]. Pregnant women with disabilities were found to be more likely to receive inadequate prenatal care than non-disabled pregnant women [21]. Several Korean studies have suggested that people with disabilities are prone to experience poverty, deprivation of human rights, social isolation, and discrimination [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Engelli kadınların, engelli olmayan kadınlara göre yetersiz doğum öncesi bakım alma olasılığı 2 kat daha fazladır (Lim, 2015). Engelli kadınlar gebelik, doğum öncesi bakım ve doğumda daha hassastır.…”
Section: Discussionunclassified
“…Engelli kadınların erken doğum riski, sezaryen oranı ve abortus hızı yüksektir ve yenidoğan bebeklerin doğum kilosu ve apgar skorunun düşük olduğu görülmektedir (Lim et al, 2015). Ayrıca tüm bu sorunların yanında, engelli kadınların cinsel sağlık ve üreme sağlığı alanında yetersiz hizmetlerden dolayı sağlık hizmetlerine erişimde zorlandıkları belirtilmektedir (Patage et al, 2015;Gibson & Mykitiuk, 2012;Thomas & Curtis, 1997;Morrison et al, 2015).…”
Section: Introductionunclassified
“…Para Lim et al (2015), as mulheres que não planejam uma gravidez, a orientação profissional é de suma importância, no sentido de garantir uma vida sexual plena, sem riscos de uma gravidez indesejada. Quando se decide gestar, ou seja, realizar um planejamento familiar, é imprescindível.…”
Section: Introductionunclassified